Analisis tingkat pengungkapan laporan keuangan pemerintah daerah kota Manado tahun 2021-2022 - Wenas, Lethisia Fransiska; Warongan, Jessy D. L.; Kindangen, Wulan D. (Riset Akuntansi dan Portofolio Investasi, 2025)
The financial statements of local governments are critical tools for providing relevant and timely information as a basis for accountability, performance evaluation and government decision-making. Appropriate levels of disclosure in financial reports are essential to ensure that the information presented can be understood by users of the financial statements. This research focuses on disclosures in the notes to the financial statements, which consist of 7 disclosure aspects with a total of 50 detailed mandatory items. In 2021-2022, the City of Manado experienced an increase in asset value and capital expenditure, which prompted the government to prepare its financial statements with a higher level of disclosure. This study aims to analyse the level of disclosure in the financial statements of the Manado Regional Government for the years 2021-2022. The data was processed using content analysis methods and the research approach used is qualitative. The results show that the level of disclosure in Manado's 2021-2022 financial statements is "very high" at 94%, indicating a significant improvement in reporting.